The Prague Hypertensive Rat: a new model of genetic hypertension - Heller, J; Hellerová, S; Dobesová, Z; Kunes, J; Zicha, J (Clinical and experimental hypertension (New York, N.Y., 1993)
Several animal models of genetic hypertension have been developed but not all of them possess a closely related control strain. Therefore, a new model based on Wistar rats is described in which both hypertensive and normotensive lines were bred from a single parental pair. Several basic data on the two lines (called the Prague Hypertensive Rat, PHR, and the Prague Normotensive Rat, PNR) are given. PNR had a longer survival compared with PHR. At the age of 7 weeks, systolic blood pressure was 161 +/- 14 mmHg in PHR males and 109 +/- 9 mmHg in PNR males. Its further increase with age was very slow in PNR but very steep in PHR. Typical left ventricular cardiac hypertrophy developed in PHR in which cardiac output was not significantly different from that of PNR but total peripheral resistance was higher. Kidney weight was also greater in PHR than in PNR. There was no difference in basic renal functions except of proteinuria which was higher in PHR than in PNR. No differences were observed in extracellular and interstitial fluid volumes whereas plasma and blood volumes were slightly but significantly greater in PHR than in PNR suggesting a shift of extracellular fluid towards the intravascular compartment. This hypertensive model the parameters of which resemble to those of human essential hypertension should be especially suitable for cross-transplantation studies.
Keywords: tělesné tekutiny; velikost orgánu; modely nemocí na zvířatech; Body Fluids; Male; hypertenze; Rats, Inbred Strains; Organ Size; potkani inbrední SHR; Kidney; mužské pohlaví; inbrední kmeny potkanů; Hypertension; krysa rodu Rattus; Animals; krevní tlak; ženské pohlaví; ledviny; zvířata; Rats; Blood Pressure; Disease Models, Animal; Rats, Inbred SHR; Female